Characterization of tin oxide based sol-gel coatings on borosilicate glasses by X-ray reflectivity - Rizzato, A. P.; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP] (Kluwer Academic Publ, 2000)
The X-ray reflectivity technique was applied in the study of tin oxide films deposited by sol-gel dip-coating on borosilicate glasses. The influence of the withdrawal speed and temperature of thermal treatment on the film structure was analyzed. We have compared the thermal evolution of the density and the shrinkage of the films with these properties measured for the monolithic xerogel by helium picnometry and thermomechanical analysis. In agreement with the Landau-Levich model, the layer thickness increases by increasing the withdrawal speed. Nevertheless, it decreases with the increase of the thermal treatment temperature, due to the densification process. The values of apparent density are smaller than the skeletal density, which shows that the films are porous. The comparison between the film and the monolith indicates that shrinkage during firing is anisotropic, occurring essentially perpendicular to the coating surface.
Keywords: SnO2 thin coatings; X-ray reflectivity; film structure; sintering